2022
DOI: 10.1097/ncc.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality as a Mediator Between Social Support and Benefit Finding Among Advanced Cancer Patients

Abstract: BackgroundSocial support and benefit finding (BF) are important for cancer patients. The relationship between social support and BF has not been studied sufficiently in patients with advanced cancer, and the mechanism through which social support might influence BF is unclear.ObjectiveThis study aimed to investigate the relationship between social support and BF in Chinese patients with advanced cancer as mediated by their perceptions of spirituality.MethodsThis was a correlation study with a cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The prevalence of negative coping strategies in our sample may re ect the particularly severe symptoms of lung cancer and our participants' relatively low disease-related knowledge, which can lead them to believe that their chemotherapy will be ineffective and their prognosis poor, in turn leading to fatalism. Such fatalism may be reinforced by traditional Chinese beliefs in the preordained nature of life and death [39]. Medical staff may be able to improve the QOL of elderly lung cancer patients by educating them about their disease and chemotherapy, alleviating the adverse effects of therapy as much as possible, and promoting the use of positive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of negative coping strategies in our sample may re ect the particularly severe symptoms of lung cancer and our participants' relatively low disease-related knowledge, which can lead them to believe that their chemotherapy will be ineffective and their prognosis poor, in turn leading to fatalism. Such fatalism may be reinforced by traditional Chinese beliefs in the preordained nature of life and death [39]. Medical staff may be able to improve the QOL of elderly lung cancer patients by educating them about their disease and chemotherapy, alleviating the adverse effects of therapy as much as possible, and promoting the use of positive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, negative emotions such as anxiety and depression were negatively correlated with BF [18,19]. Moreover, previous studies have reported that BF is positively correlated with social support [20], positive coping [21] and general self-efficacy [11] in patients. Specifically, the perceived social support of individuals may not be equal to the social support they actually receive [22], but positive coping may lead patients to more easily perceive social support, so as to more actively deal with negative events and improve BF [12].…”
Section: Introductionmentioning
confidence: 89%
“…Relevant studies have demonstrated a positive correlation between social support and bene t ndings among cancer patients [13]. Nevertheless, most prior studies have concentrated more on the patients and neglected the caregivers with the primary caregiving responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…In general, this study aimed to discuss the dyadic effects of social support and hope level on bene t nding in advanced lung cancer patient-caregiver dyads. Based on the literature review and theoretical support [13,17], we postulated that, in advanced lung cancer patient-caregiver dyads, social support and hope level were connected with bene t ndings, and the association between social support and bene t nding was mediated by hope level.…”
Section: Introductionmentioning
confidence: 99%